MUSLIM KANAYATN: MINORITY IDENTITY DISORDER - Zulkifli, Zulkifli; Prasojo, Zaenudin Hudi; Sahrin, Mohammed (Analisa: Journal of Social Science and Religion, 2019)
In the past people identified the dayak, especially sub ethnic of Kanayatn as Christians or Catholics. By the time and the rapid progress of the Kanayatn communities in their religious aspect, there was also a change of faith. Since the 1980s several Kanayatn people started converting to Islam or mualaf. To reveal how the existence of those who live as minority Muslims in the midst of the Kanayatn who are still Christian or Catholic, this study was done using a qualitative approach with a case study design. The location of the study was in the remote area in West Kalimantan, precisely in Sidas Village, Sengah Temilah District, Landak Regency.  Result of the study showed that after the Kanayatn people converted to Islam, they are experiencing a breakdown of identity. Their existence is accepted by halfhearted both by the Kanayatn and Malay communities. The Malay community in general are still perpetuating them as "converts". Meanwhile the Kanayatn community (Christian community) considers them as Malay or descendant of Malay. Nevertheless, Kanayatn people who convert to Islam try to maintain their identity as Kanayatn people who are Muslim or in short Muslim Kanayatn. Other findings show that as the minority where they are lack of religious guidance, the Muslim community of Sidas Village must be smart in responding to the situation so that they can survive and coexist peacefully among of the  Christian majority.